2018
DOI: 10.1017/s0950268818001553
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, antimicrobial susceptibility patterns and genotypic relatedness of Salmonella spp. isolates from captive wildlife, their caretakers, feed and water in India

Abstract: Occurrence of Salmonella spp. in captive wild animal species in India is largely unknown. The purpose of this study was to determine the occurrence of different Salmonella serotypes, antimicrobial resistance patterns and genotypic relatedness of recovered isolates. A total of 370 samples including faecal (n = 314), feed and water (n = 26) and caretakers stool swabs (n = 30) were collected from 40 different wild animal species in captivity, their caretakers, feed and water in four zoological gardens and wildlif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In our study, 78.0% (32/41) of isolates were pansusceptible, while the remaining 22.2% (9/41) were resistant to at least one antibiotic; no multiresistance profiles were found. This matches with previous wildlife studies where the frequency of antibiotic use is low compared to livestock and healthcare settings [13]. Although wildlife is unlikely to be treated with antibiotic therapy, when they enter one of these rescue sites, it is mostly because they have a health condition, which may require the use of antibiotics [52].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, 78.0% (32/41) of isolates were pansusceptible, while the remaining 22.2% (9/41) were resistant to at least one antibiotic; no multiresistance profiles were found. This matches with previous wildlife studies where the frequency of antibiotic use is low compared to livestock and healthcare settings [13]. Although wildlife is unlikely to be treated with antibiotic therapy, when they enter one of these rescue sites, it is mostly because they have a health condition, which may require the use of antibiotics [52].…”
Section: Discussionsupporting
confidence: 87%
“…S. Kentucky is involved in approximately 100 cases of human salmonellosis yearly in the United States ( Centers for Disease Control and Prevention [CDC], 2016 ). Although it is not one of the leading serovars causing human salmonellosis, there is increasing concern with the emergence of multidrug resistance particularly associated with this serovar ( Milton et al, 2018 ; Al-Gallas et al, 2021a , b ). On the other hand, S. Rubislaw has been mainly detected in environmental samples ( Maurer et al, 2015 ), and various free-living animals ( Potter et al, 2011 ; Rush et al, 2020 ; Hernandez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The isolates from wild animals show a similar pattern of drug resistance to E. coli from human clinical sources in their study areas ( Jobbins and Alexander, 2015 ). Other studies have indicated that drug-resistant Salmonella isolates identified from zoo environments, including those from animals and their keepers, have been confirmed to be clone-related ( Farias et al, 2015 ; Milton et al, 2018 ). Therefore, wild animals may be important hosts and storage hosts for the spread of drug-resistant bacteria, and human activities significantly affect the microbial community of captive wild animals in zoo environments, which are not necessarily monitored for such risks.…”
Section: Discussionmentioning
confidence: 99%